Using hermeneutics to inform bibliometric research: A mixed methods approach - Kelly, Matthew (Qualitative and Quantitative Methods in Libraries, 2017)
The problem of bringing semantic context to subject categories as expressed in ontologies such as the OCLC Conspectus—when the goal is to understand the overall epistemic message that the expression of selection decisions aimed at a particular branch of knowledge with varying degrees of scope and depth provides— is a difficult undertaking both in terms of finding ways to interpret the relationship between subject domains and to impose reasons for the choice. It is argued here that there are significant areas of shared interest in hermeneutically and phenomenologically informed philosophy of social science and naturalistic equivalents and that a pluralist approach is appropriate to tackling the methodological issues associated with interpretation and systematisation in bibliometrics. Through the prism of phenomenological realism, a mind-independent view of the categories objectivated by the research is maintained as is the possibility that this can co-exist with active perception and reflection to reveal the complexity inherent in simple categorisation.